(untitled) (Texas Journal of Medical Science, 2023)
Reproduction of offspring is a complex biological process in which not only the reproductive apparatus, but the entire organism as a whole is involved. Therefore, the causes leading to reproductive dysfunction must be sought not only in the reproductive system, but throughout the entire body.